A depth-averaged model for non-isothermal thin-film rimming flow - Kay, E.D.; Hibberd, Stephen; Power, H. (Elsevier, 2014)
A model for non-isothermal shear-driven thin-film flow on the inside surface of a stationary circular cylinder is presented. Motivated by an application to film flow in an aero-engine bearing chamber the model extends lubrication theory analysis of thin films to retain the important effects of inertia and heat convection.The accuracy of the depth-averaged temperature model is tested and comparisons illustrate the model is accurate for both conduction- and convection-dominant flows although local inaccuracies are introduced in regions exhibiting sharp changes in boundary temperature when convective effects are strong.Three rimming-flow configurations are considered: uni-directional flow with slowly-varying film height, a solution containing a steep front termed a shock, and a pooling solution where fluid accumulates in a recirculation at the base of the cylinder. The temperature field in the latter two which include recirculation features are greatly influenced by the strength of convection in the film.